An??lise da express??o g??nica de componentes do sistema calicre??na-cininas em dep??sitos adiposos em sujeitos com s??ndrome de Cushing - Sousa, Dannylo Wesley N??brega de (2011)
Glucocorticoids (GC) play an important role in determining the distribution of adipose tissue and metabolism. Individuals with Cushing's syndrome (CS) show a pattern of central obesity, related to excessive levels of plasma glucocorticoids exogenous or endogenous origin which is reversible after treatment or withdrawal of corticosteroids. The mechanisms involved in the distribution of adipose tissue mediated by glucocorticoids are not fully understood. The objective of this study was to quantify and evaluate the effects of chronic exposure to hypercortisolism in the gene expression of components of the kallikrein-kinin fat deposits in patients with Cushing's Syndrome. Samples of visceral (VAT) and subcutaneous adipose tissue (SAT) were obtained during elective abdominal surgery for female patients with Cushing's Syndrome (n = 9), in which the body mass index (BMI), waist circumference (WC) and salivary cortisol (CTS) were previously determined. The mRNA expression of tissue kallikrein and the kinin B1 and B2 receptors were quantified by real-time PCR. The mRNA expression of kinin B2 receptor in SAT and VAT of Cushing's patients was similar in both compartments (p> 0.05). The expression of kinin B1 receptor was reduced in SAT when compared to VAT of patients with Cushing (p <0.01). The expression of tissue kallikrein showed a significant increase in VAT than observed in SAT of patients with Cushing s Syndrome (p <0.05). Our data suggest that chronic hypercortisolism, as seen in Cushing's Syndrome, is related to an increased mRNA expression of kinin B1 receptor and tissue kallikrein in visceral adipose tissue (VAT), the main compartment responsible for complications related to obesity and high mortality, while the gene expression of kinin B2 receptor remained unchanged in both compartments.